Consumption rates of the periwinkle Littorina obtusata on the brown seaweed Ascophyllum nodosum - Carla Rebecca Flöthe; Markus Molis (PANGAEA, 2013)
Anti-herbivory defenses support persistence of seaweeds. Little is known, however, about temporal dynamics in the induction of grazer-deterrent seaweed traits. In two induction experiments, consumption rates of the periwinkle Littorina obtusata (L.) on the brown seaweed Ascophyllum nodosum (L.) Le Jolis were measured in 3-d intervals. Changes in palatability of directly grazed A. nodosum were tested every 3 d with feeding assays using fresh and reconstituted seaweed pieces. Likewise, assays with fresh A. nodosum assessed changes in seaweed palatability in response to water-borne cues from nearby grazed conspecifics. Consumption rates of L. obtusata varied significantly during the 27-d induction phase of each experiment. Direct grazing by L. obtusata lowered palatability of fresh and reconstituted A. nodosum pieces to conspecific grazers after 15 d as well as after 6 and 12 d, respectively. After 12, 18, and 24 d, fresh A. nodosum located downstream of L. obtusata-grazed conspecifics was significantly less palatable than A. nodosum located downstream of ungrazed conspecifics. Changes in L. obtusata consumption rates and A. nodosum palatability during both induction experiments suggest temporal variation of grazer-deterrent responses, which may complicate experimental detection of inducible anti-herbivory defenses.
Supplement to: Flöthe, CR; Molis, M (2013): Temporal dynamics of inducible anti-herbivory defenses in the brown seaweed Ascophyllum nodosum (Phaeophyceae). Journal of Phycology, 49(3), 468-474, https://doi.org/10.1111/jpy.12059